Strategic and entrepreneurial abilities: Surviving the crisis across countries during the Covid-19 pandemic. - Paweł Chudziński; Szymon Cyfert; Wojciech Dyduch; Salah Koubaa; Maciej Zastempowski (PLoS ONE, 2023)
This paper seeks to identify organisational abilities that influence the company's survival during crises. To address this issue, first-through literature review-we identified five groups of crucial organisational abilities that companies pursue during the crisis, i.e., strategic, technological, collaboration, entrepreneurial and relational. We have also identified four objectives that relate to surviving the crisis. Next, we have scrutinised 226 companies from two sides of the world, Poland (Europe) and Morocco (Africa), during the Covid-19 crisis. Quantitative analysis using Structural Equations Modelling demonstrated that surviving during a crisis depends mostly on strategic and entrepreneurial abilities such as the ability to shift resources quickly, organise the work in the firm effectively and plan strategically, as well as diversify its products and services perceived as critical.